2020
DOI: 10.1002/lio2.345
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal strategy for the management of sphenoid osteoradionecrosis: Preliminary results

Abstract: Objective Osteoradionecrosis (ORN) of the sphenoid is a rare but potentially lethal complication that can occur after irradiation of nasopharyngeal and clival malignancies. The objective of this study was to describe a multimodal treatment strategy tailored to the clinical signs and to the radiological extent of the disease, and to report on its preliminary results. Methods Retrospective monocentric study at a tertiary skull base center. Patients treated for a sphenoid ORN from January 2014 to August 2018 were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(33 citation statements)
references
References 12 publications
1
32
0
Order By: Relevance
“…This study is the first systematic review and meta‐analysis focusing on disease resolution and major complication rates after ESBS in the management of skull base ORN. The pooled resolution rate of 64% identified in this analysis is in agreement with the literature showing that ESBS is an effective treatment approach for skull base ORN, providing adequate access and reconstructive options 1–3,6–10 . However, there was significant heterogeneity in the data, which may be attributed to the fact that the a priori definitions of efficacy were inconsistent between studies.…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…This study is the first systematic review and meta‐analysis focusing on disease resolution and major complication rates after ESBS in the management of skull base ORN. The pooled resolution rate of 64% identified in this analysis is in agreement with the literature showing that ESBS is an effective treatment approach for skull base ORN, providing adequate access and reconstructive options 1–3,6–10 . However, there was significant heterogeneity in the data, which may be attributed to the fact that the a priori definitions of efficacy were inconsistent between studies.…”
Section: Discussionsupporting
confidence: 86%
“…8 Notably, several studies reported worse outcomes in patients who underwent multiple courses of radiotherapy due to local NPC recurrence. [1][2][3]7,8 In the largest study included in this analysis, multiple radiotherapy courses was an independent negative predictor of overall survival after ESBS (p = 0.026), with a mortality rate 3.2-fold higher than for patients with a single course. 8 Only 1 study reported major complications after ESBS, which occurred in 3 patients.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations